(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of the current research is to determine the level of academic achievement motivation of the students in the national center for distinguished in Syria. In addition to determining whether the level of academic achievement motivation varies according to the stage of study or gender or the desire to join the Center. In order to achieve the objectives of the research, the descriptive approach was adopted. The motivation scale was distributed to a sample of 170 students at the National Center for distinguished in the academic year 2015-2016. The results showed that 74% of respondents had an average level of academic achievement motivation, 24% had a high level and 1.76% had a low level. Also, this level did not differ according to the stage of study or sex, but differed according to the students’ desire to join the center. Students who joined the center with their personal desire or with a common desire between them and the parents were more motivated to achieve than students who joined the center with a desire of their parents without theirs.